2019
DOI: 10.1108/jes-11-2017-0343
|View full text |Cite
|
Sign up to set email alerts
|

The role of inclusive development and military expenditure in modulating the effect of terrorism on governance

Abstract: Purpose The purpose of this paper is to investigate the role of inclusive human development and military expenditure in modulating the effect of terrorism on governance. Design/methodology/approach It is based on 53 African countries for the period 1998–2012 and interactive generalised method of moments is employed. Six governance indicators from the World Bank and two terrorism variables are used, namely, domestic and transnational terrorism dynamics. Findings The following main findings are established. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 141 publications
(233 reference statements)
0
4
0
Order By: Relevance
“…Terrorist activities create vulnerability, uncertainty, and panic in the overall environment of a country (Aslam & Kang, 2015;Asongu et al, 2018) and adversely affect the economy of a country by damaging essential infrastructure, causing financial instability, decreasing the confidence of investors and foreign direct investment (FDI) inflows, and increasing counter-terrorism costs (Aisha & Shehla, 2014;A. Ali, 2010;Bano et al, 2019;X.…”
Section: Introductionmentioning
confidence: 99%
“…Terrorist activities create vulnerability, uncertainty, and panic in the overall environment of a country (Aslam & Kang, 2015;Asongu et al, 2018) and adversely affect the economy of a country by damaging essential infrastructure, causing financial instability, decreasing the confidence of investors and foreign direct investment (FDI) inflows, and increasing counter-terrorism costs (Aisha & Shehla, 2014;A. Ali, 2010;Bano et al, 2019;X.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation coefficient of 0.99 between the dependent variable (LCAF) and its first lag (L.LCAF) indicates the presence of persistence in the explained variable. Coefficient above 0.8 is an indication that GMM is an appropriate technique (Asongu et al , 2019;Tchamyou and Asongu, 2017; Tchamyou et al , 2019; Blundell and Bond, 1998). When the correlation test produces close to perfect coefficient, then multicollinearity exists.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…This condition was tested and met in this study. This study also followed Asongu et al (2019), Tchamyou and Asongu (2017); Tchamyou et al (2019), Blundell and Bond (1998) to statistically select the apposite variant of the GMM techniques to adopt. Blundell and Bond (1998), Bond and Hoeffler (2001) suggested that to use either the DGMM or the SGMM, both the pooled OLS (POLS) and fixed-effect (FE) model as well as the DGMM should be estimated.…”
Section: Model Specificationmentioning
confidence: 99%
“…Against this backdrop, a growing body of literature has focused on investigating tools with which conflicts and terrorism can be attenuated (if not eradicated). Some of the documented mechanisms have encompassed, channels of: education (Brockhoff et al, 2014), especially lifelong learning (Asongu & Nwachukwu, 2016b) and bilingualism (Costa et al, 2008); the rule of law (Choi, 2010); the appealing role of the media and freedom of the press (Hoffman et al, 2013); behavourial motivations underpinning terrorism (Gardner, 2007) and employment of military devices (Feridun & Shahbaz, 2010;Asongu & Amankwah-Amoah, 2018;Asongu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%